Your Beauty Guide App: Smart Makeup Assistant - Abdul Khalid, Aryssa Batrisya; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2026)
The Your Beauty Guide App: Smart Makeup Assistant is an AI-powered solution designed to simplify makeup selection for diverse skin tones and types, eliminating mismatched products and unreliable advice. Using AI, it analyzes skin tone, type, and facial structure to offer personalized recommendations and techniques, enhancing natural beauty and inclusivity. Developed via the Waterfall Model (analysis, design, implementation, testing, maintenance), the app ensures systematic progress. Built with Flutter, it supports cross-platform use on Windows 11 and mobile devices. Key features include skin detection, tailored recommendations, and history tracking, reducing reliance on biased beauty advisors. Development involved UML diagrams, database schemas, and UI mockups, followed by AI integration and rigorous testing for accuracy. The app successfully minimizes trial-and-error purchases, offering a user-centric, AI-driven beauty experience. Future enhancements may include expanded AI learning and advanced customization, showcasing how technology can make makeup selection inclusive, efficient, and personalized.